Experimental in situ investigations of turbulence under high pressure - Song, Kwonyul; Al-Salaymeh, Ahmed; Jovanovic, Jovan; Rauh, Cornelia; Delgado, Antonio (Annals of the New York Academy of Sciences, 2010)
In tube injection systems applied in high-pressure processing of packed biomaterials and foods, the pressure-transmitting medium is injected into the vessel to increase the pressure up to 1000 MPa, generating a submerged liquid-free jet. The presence of a turbulent-free jet during the pressurization phase and its positive influence on the homogeneity of the product treatment has already been examined by computational fluid dynamics investigations. However, no experimental data have supported the existence and properties of turbulent flow under high-pressure (HP) conditions up to 400 MPa. This contribution presents the development of two experimental setups: HP-laser Doppler anemometry and HP-hot wire anemometry. For the first time the time-averaged velocity profiles of a free jet during pressurization up to 300 MPa at different Reynolds numbers (Re) have been obtained. In this article, the dependence of the velocity profiles on the Re is discussed in detail. Moreover, the relaminarization phenomenon of the turbulent pipe flow most likely caused by the compressibility effects and viscosity changes of the pressure-transmitting medium is examined. © 2010 New York Academy of Sciences.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.experi_4
Keywords: High pressure; Hotwire anemometry; Laser Doppler anemometry; Turbulence